The relationship between worry and intolerance of uncertainty subtypes. (17th July 2019) - Groves, David; Clark, Laura H.; Clark, Gavin I.
Abstract: Objective: According to the intolerance of uncertainty model (IUM) of generalised anxiety disorder (GAD), four components contribute to the development and maintenance of worry in GAD. They are intolerance of uncertainty (IU), positive beliefs about worry, negative problem orientation, and cognitive avoidance. Recent studies report that the relationship between IU and worry is mediated by positive beliefs about worry and negative problem orientation. The present study examined whether these mediation relationships emerge when the two subtypes of IU, prospective and inhibitory IU, are considered separately. Method: A convenience sample of 160 members of the Australian public completed an online questionnaire assessing each IUM component, worry, and depression. Results: Positive beliefs about worry and negative problem orientation mediated the relationship between IU and worry. Only positive beliefs about worry mediated the relationship between prospective IU and worry, while only negative problem orientation mediated the relationship between inhibitory IU and worry. Conclusions: The results may imply that the two IU subtypes influence worry via differing pathways. The findings have implications for treatments targeting components of the IUM in individuals with GAD and other anxiety disorders.